2006
DOI: 10.1097/01.shk.0000215320.06866.30
|View full text |Cite
|
Sign up to set email alerts
|

Altered Hemodynamic Counter-Regulation to Hemorrhage by Acute Moderate Alcohol Intoxication

Abstract: The incidence of traumatic injury, frequently associated with hemorrhagic shock, is higher in the alcohol-intoxicated individual. The outcome, as it pertains to both morbidity and mortality of this population, is partly dependent on duration of alcohol exposure and levels of blood alcohol at time of injury. In previous studies, we demonstrated that prolonged alcohol intoxication (15-h duration) produces marked hemodynamic instability and exacerbated early lung proinflammatory cytokine expression after hemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
1
22
1
Order By: Relevance
“…In agreement with previous reports from our laboratory, TÂHem produced an early induction of lung and spleen cytokine (TNF-a and IL-1a) expression (Mathis et al, 2006;Phelan et al, 2002). Alcohol binge blunted the magnitude of the TÂHem-induced increase in lung TNF-a but did not produce significant alteration of the lung IL-1a response or of the spleen TNF-a and IL-1a response.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In agreement with previous reports from our laboratory, TÂHem produced an early induction of lung and spleen cytokine (TNF-a and IL-1a) expression (Mathis et al, 2006;Phelan et al, 2002). Alcohol binge blunted the magnitude of the TÂHem-induced increase in lung TNF-a but did not produce significant alteration of the lung IL-1a response or of the spleen TNF-a and IL-1a response.…”
Section: Discussionsupporting
confidence: 90%
“…Alcohol binge blunted the magnitude of the TÂHem-induced increase in lung TNF-a but did not produce significant alteration of the lung IL-1a response or of the spleen TNF-a and IL-1a response. This is in contrast to our previous observations in animals that received a continuous 15-hour infusion in which tissue proinflammatory responses to hemorrhage were accentuated (Phelan et al, 2002) but similar to the effects produced by a single dose of alcohol administered before hemorrhage (Mathis et al, 2006). These apparently disparate effects of alcohol on immune responses have been attributed to differential duration of alcohol exposure, with acute alcohol resulting in most cases in suppression of proinflammatory responses (Boe et al, 2001;Szabo, 1999;Zhang et al, 2002) and chronic alcohol exposure favoring a proinflammatory response (Bautista, 1995;Diehl, 1998;Yang et al, 1998).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Alcohol-intoxicated trauma patients enter the emergency department more hypotensive than their sober counterparts (41). Clinical data suggest that mean arterial blood pressure (MABP) at the time of admittance into the emergency department is one of the most critical indicators of a patient's outcome and survival from traumatic injury and blood loss (15); therefore, the greater hypotension noted in alcohol-intoxicated trauma patients is likely to contribute to their increased morbidity and mortality.Previously, we demonstrated that acute intoxication produced by intragastric administration of alcohol decreases baseline MABP, accentuates hypotension throughout hemorrhage, and blunts the pressor response to fluid resuscitation, regardless of the dose (1.75, 5, and 8 g/kg) and frequency (single dose, 3-day binge, and 15-h constant infusion, respectively) of alcohol administration (12,25,26,30,33). This impaired hemodynamic compensatory response to hemorrhage in alcohol-intoxicated rats is associated with suppression of catecholamine (epinephrine and norepinephrine) and AVP responses (30).…”
mentioning
confidence: 98%
“…Previously, we demonstrated that acute intoxication produced by intragastric administration of alcohol decreases baseline MABP, accentuates hypotension throughout hemorrhage, and blunts the pressor response to fluid resuscitation, regardless of the dose (1.75, 5, and 8 g/kg) and frequency (single dose, 3-day binge, and 15-h constant infusion, respectively) of alcohol administration (12,25,26,30,33). This impaired hemodynamic compensatory response to hemorrhage in alcohol-intoxicated rats is associated with suppression of catecholamine (epinephrine and norepinephrine) and AVP responses (30).…”
mentioning
confidence: 98%